2005
DOI: 10.1007/s00125-005-1887-z
|View full text |Cite
|
Sign up to set email alerts
|

Acute glucosamine-induced insulin resistance in muscle in vivo is associated with impaired capillary recruitment

Abstract: Aims/hypothesis: Glucose toxicity and glucosamine-induced insulin resistance have been attributed to products of glucosamine metabolism. In addition, endothelial cell nitric oxide synthase is inhibited by glucosamine. Since insulin has endothelial nitric-oxide-dependent vasodilatory effects in muscle, we hypothesise that glucosamine-induced insulin resistance in muscle in vivo is associated with impaired vascular responses including capillary recruitment. Materials and methods: Glucosamine (6.48 mg kg −1 min −… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
30
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 56 publications
(93 reference statements)
1
30
0
Order By: Relevance
“…potential mechanism for hyperglycemia to contribute to development of both insulin resistance and endothelial dysfunction (13,(15)(16)(17)(18)(19)(20)(21)23,24,(35)(36)(37)(38). Indeed, treatment of cells in vitro with glucosamine (1-10 mmol/l) causes both insulin resistance and endothelial cell dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…potential mechanism for hyperglycemia to contribute to development of both insulin resistance and endothelial dysfunction (13,(15)(16)(17)(18)(19)(20)(21)23,24,(35)(36)(37)(38). Indeed, treatment of cells in vitro with glucosamine (1-10 mmol/l) causes both insulin resistance and endothelial cell dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, treatment of cells in vitro with glucosamine (1-10 mmol/l) causes both insulin resistance and endothelial cell dysfunction. More importantly, intravenous infusions of glucosamine that achieve plasma concentrations of 0.5-1.8 mmol/l in both animals and humans causes insulin resistance and endothelial dysfunction (20,25). Thus, there are significant potential safety concerns associated with glucosamine therapy for osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown that acute defects in insulin-mediated microvascular recruitment can contribute to the development of muscle insulin resistance in vivo. Infusion of α-methyl serotonin [26], endothelin-1 [27], L-N G -Nitroarginine methyl ester [7,29,37], TNFα [38], Intralipid® plus heparin [39] and glucosamine [40] in healthy animals attenuate insulin-mediated microvascular recruitment and insulin-mediated muscle glucose uptake. In addition, chronic models of insulin resistance including the high fat-fed rat (36% fat wt/ wt) [3], and obese Zucker rat [41] display marked attenuation in insulin-mediated microvascular recruitment and muscle glucose uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced delivery of insulin and glucose would give rise to a reduced R d and HLGU. Based on previous studies where insulin-mediated capillary recruitment has been blocked by a 5-hydroxytryptamine agonist (25), tumor necrosis factor-␣ (40), free fatty acids (7), or glucosamine (34), this could amount to ϳ50% inhibition of the insulin-mediated increase in muscle glucose uptake, with the expectation of a similar magnitude of inhibition of R d and muscle P-Akt/Akt. In addition to this, it appears likely that the relatively water-insoluble wortmannin is unable to fully diffuse to those myocytes that are unaffected by capillary recruitment (i.e., where insulin delivery is unrestricted).…”
Section: Discussionmentioning
confidence: 99%